Global patterns of change in the burden of malnutrition in older adults from 1990 to 2021 and the forecast for the next 25 years - Li, Le; Liu, Xiao; Fang, Yujie; Guo, Kailin; Li, Lu; Cai, Shuhan; Hu, Chang; Hu, Bo (Frontiers in Nutrition, 2025)
BackgroundMalnutrition poses a significant public health challenge, particularly as the global population ages. However, there is a notable lack of comprehensive literature analyzing the global burden of malnutrition among the elderly.MethodsData on nutritional deficiencies indicators—prevalence, incidence, and disability-adjusted life years (DALYs)—for individuals aged 70 and older were extracted from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) database from 1990 to 2021. The estimated annual percentage change (EAPC) was used to assess trends in malnutrition burden. Predictions for new cases over the next 25 years were also made.ResultsIn 2021, over 97.60 million cases of malnutrition among the elderly were reported globally, a 1.2-fold increase from 44.36 million cases in 1990. The global prevalence rate of malnutrition has decreased with an EAPC of −0.32%. Women experienced more cases than men but had a lower prevalence rate. Furthermore, in high socio-demographic index (SDI) regions, both prevalence rate and DALYs rates increased from 1990 to 2021, with EAPCs of 0.33% and 1.34%, respectively. The burden of malnutrition in the elderly was negatively correlated with SDI. Predictions from 2022 to 2046 estimated approximately 29.64 million new cases of malnutrition by 2046, despite a declining incidence rate.ConclusionDespite a decline in malnutrition prevalence rate and DALYs rate since 1990, the burden remains high, particularly in high SDI regions where rates have increased. With a projected rise in new cases, effective prevention and management strategies are urgently needed to support the health of older adults.